Managing agricultural water-energy-food-environment nexus considering water footprint and carbon footprint under uncertainty - Yue, Qiong; Guo, Ping (Agricultural water management, 2021)
Water, energy, food, and environment are highly interconnected, with intricate dependencies and multiple uncertainties involved in agricultural system. This paper presents a novel water-energy-food-environment nexus (WEFEN) optimization model for sustainable development of agriculture. The developed model incorporates stochastic multi-objective programming, triangular fuzzy numbers, fuzzy credibility-constrained programming, mixed-integer programming, non-linear programming, and Stewart model into a general optimization framework. The model is capable of (1) balancing the tradeoffs among socio-economic, resources, and environmental concerns; (2) generating valid WEFEN management solutions achieving the targets of maximum net economic benefit, maximum renewable energy production, minimum water footprint, and minimum carbon footprint simultaneously; (3) dealing with complexities and uncertainties existed in agricultural WEFEN systems. The model was applied to the Zhanghe irrigation district to give policy-makers insights into what efforts should be made towards sustainable agricultural management. Flexible alternatives were generated under different scenarios and sensitivity analyses were conducted. Results highlighted the significance of improvement of internal water storage capacity, reasonable farmland management, and compromise decision preferences. The proposed methodology is applicable for other agriculture-centered regions suffering from multifold resources and environment crisis. •Interactions among water-energy-food-environment nexus (WEFEN) are quantified.•Inexact multi-objective optimization model for managing WEFEN system is developed.•Tradeoffs among social-economic, resources, and environmental impacts are addressed.•Complexities and uncertainties in agricultural WEFEN system are tackled.•Insights into sustainable agriculture are provided for Zhanghe irrigation district.